Losing the Country: Debt, Deflation, and the Rural Rise of the Nazi Party - Thilo N. H. Albers; Felix Kersting; Monique Reiske (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2024)
Using interwar German agriculture as a case, this paper explores the political cost of debt deflation which we characterize with farmers' leverage ratios. Primary deficits drove their increase during 1924-1928, but deflation pushed them to unsustainable levels during 1929-1932. We construct corresponding exogenous county-level exposure measures and show their effect on economic distress as well as political radicalization. Our results suggest that debt deflation increased the Nazi party's rural vote share by over 8 percentage points relative to a counterfactual baseline scenario and was thus a necessary condition for its rural dominance and ascension to parliamentary power.
Keywords: D72; N13; N54; 330; Great Depression; Weimar Germany; NSDAP; extremism; debt deflation; economic crisis